The effect of knowledge level on childbirth on the anxiety level of mothers during delivery - Pedrosa, John Mark
This study focused on the relationship between the knowledge level on childbirth of mothers and their anxiety level during delivery. The subjects included thirty mothers on their late transitional phase of labor admitted in two of the selected lying-in clinics in Manila. Using an observation checklist, they were observed while delivering. Their vital signs were also monitored every five minutes as an adjunct to the anxiety level indicator. They answered an interview questionnaire measured their knowledge level on childbirth process covering all the four stages of labor and delivery. Their knowledge and anxiety levels were then correlated using the Pearson’s Rank Correlation Coefficient. The findings indicated a low negative correlation between these two variables, thus, showing no significant relation. However, this implies that other factors affecting the anxiety level of delivering mothers should also be considered in providing holistic care for patients.